2001
DOI: 10.1038/modpathol.3880473
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived Chemokine Expression in Classical Hodgkin's Lymphoma: Application of Tissue Microarrays

Abstract: Hodgkin's disease (HD) is a lymphoid malignancy characterized by the presence of Reed-Sternberg (RS) and Hodgkin's cells in a background of mixed inflammatory cells and stromal reaction. Studies have documented that HD is a neoplasm associated with abnormal cytokine and chemokine production. To define the expression of macrophagederived chemokine (MDC) in HD, 57 cases (18 lymphocyte predominant, 11 mixed cellularity, 28 nodular sclerosis) were stained for MDC by immunohistochemistry and compared with reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 21 publications
4
30
1
Order By: Relevance
“…49 By IHC, 87% of cHL cases demonstrated MDC expression, primarily localized to RS cells. 55 Eotaxin expression is higher in cHL tissues than in normal lymphoid tissues, as demonstrated by RT-PCR. 49 Within cHL subtypes, elevated eotaxin expression was preferentially associated with NSHL cases.…”
Section: Th2 Chemokinesmentioning
confidence: 75%
“…49 By IHC, 87% of cHL cases demonstrated MDC expression, primarily localized to RS cells. 55 Eotaxin expression is higher in cHL tissues than in normal lymphoid tissues, as demonstrated by RT-PCR. 49 Within cHL subtypes, elevated eotaxin expression was preferentially associated with NSHL cases.…”
Section: Th2 Chemokinesmentioning
confidence: 75%
“…Different groups in several types of human tumors have previously demonstrated the suitability of this technique. To our knowledge, a single limited study 24 has previously provided evidence of the feasibility of this tool in HL, based solely on the expression of a single protein.…”
Section: Discussionmentioning
confidence: 99%
“…However, the feasibility of this technique for analyzing highly heterogeneous tumors such as HL remains to be elucidated. Recent studies using TMA 24 have shown the potential of this technology for restricted analyses in HL.…”
Section: Introductionmentioning
confidence: 99%
“…Core needle biopsies of pre-existing paraffin-embedded tissue were obtained and then re-embedded in an arrayed master block using techniques originally developed by Kononen et al 10 and then modified by Hedvat et al 11 We used the Beecher Instruments (Sun Prairie, WI, USA) arraying device to produce sample circular spots that were 0.6 mm in diameter. Three core needle specimens were obtained from each tumor and companion tissue specimen.…”
Section: Tumor Microarraysmentioning
confidence: 99%